Pengesahan Penggabungan, Peleburan dan Pengambilalihan (P3) dan Kedudukan Konsultasi Hukum Persaingan Usaha - Yakub Adi Krisnanto (Jurnal Hukum PRIORIS, 2012)
Establishment of the Business Competition Act, particulary those governing the merger, consolidation and acquisition give birth to a legal vacumm. Notification system adopted pursuant to Article 29 paragraph (2) Competition Act, namely post notification. Competition Act further mandates the setting of the merger, consolidation and acquisition through government regulation. 10 years required for the issuance of the aforementioned, and prior to any governmnet regulation of Article 29 paragraph (2) Competition Act became lex imperfecta. The provisions on merger, consolidation and takeovers can not be applied, so that many of the alleged violation of monopolistic practices and unfair competition can not be assessed under these provisions. This paper is about to review the authorization merger, consolidation and takeover business entity in which the rules and regulations perudang be one issue of the notification system adopted in the competititon law in Indonesia. Authorization is still a problem despitethe normative level rise of government regulation on merger, consolidation and takeovers.